The Effectiveness of the Contextual Learning Model Assisted by Hands On Student Learning Outcomes - Dian Ulfa Sari; Sufri Mashuri; Resky Amalia; Deti Sri Rahayu (USN Kolaka, 2021)
This study aims to determine the effectiveness of the contextual learning model assisted by hands on problem solving in improving students' mathematics learning outcomes. The population in this study were all seventh grade students of SMP Negeri 1 Latambaga. Sampling in this study used cluster random sampling. Data collection techniques were carried out by giving tests in the form of description tests and non tests. Data were analyzed using descriptive statistics and inferential statistics with hypothesis testing using independent t-test. The results of inferential research using the t-test have been obtained value t count = ( 14 , 698 ) > t table = ( 1 , 670 ) or H, rejected. This shows that the contextual learning model assisted by hands on problem solving is effective in improving student learning outcomes.